Local Ecological Knowledge and Importance of Bakeapple (Rubus chamaemorus L.) in a Southeast Labrador Métis Community - Amanda L. Karst; Nancy J. Turner (Ethnobiology Letters, 2011)
Bakeapple, or cloudberry (Rubus chamaemorus L.; Rosaceae) is a circumpolar perennial with orange aggregate fruits, which has been a vital food resource for many northern peoples including those of the Subarctic and Arctic areas of North America. This study documented the importance and local knowledge of bakeapple in the predominantly Métis community of Charlottetown, Labrador. The cultural importance of bakeapple is evidenced by the social customs surrounding its picking, by its prevalence in people’s homes and at community events, and by its formal and informal economic exchange, within and outside the community. The local ecological knowledge of bakeapple that residents of Charlottetown possessed also illustrates its importance. Local knowledge of interviewees included different habitat types associated with various bakeapple densities and fruit sizes, bakeapple development/phenology (e.g., “turned in” stage) and variations in the berry (e.g. in color and size). Bakeapple remains a culturally important species with a high profile in Charlottetown, although lack of interest in bakeapple picking by younger people may affect future use.